2007
DOI: 10.1021/cm070818k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CdSeS Nanocrystals in Coordinating and Noncoordinating Solvents:  Solvent's Role in Evolution of the Optical and Structural Properties

Abstract: CdSe x S y nanocrystals were synthesized in eight solvents that have different coordinating properties, trioctylphosphine oxide, trioctylphosphine, triphenylphosphine, oleylamine, hexadecylamine, dioctylamine, trioctylamine, and 1-octadecene at 230−300 °C. These nanocrystals exhibited high photoluminescence, which could be tuned over most of the visible region by changing the Se/S ratio or the solvent. The nanocrystals were characterized using UV−vis and IR spectroscopy, TEM, EDS, XRD, and NMR. 31P NMR and IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 76 publications
8
91
0
1
Order By: Relevance
“…The PL emission of ternary alloyed QDs (e.g., CdSe x Te 1-x , CdS x Se 1-x , Cd x Zn 1-x S, Cd 1-x Zn x Se) can be varied while maintaining a constant size (Fig. 1D), [51][52][53][54][55][56] and these materials are also commercially available.…”
Section: Quantum Dot Materialsmentioning
confidence: 99%
“…The PL emission of ternary alloyed QDs (e.g., CdSe x Te 1-x , CdS x Se 1-x , Cd x Zn 1-x S, Cd 1-x Zn x Se) can be varied while maintaining a constant size (Fig. 1D), [51][52][53][54][55][56] and these materials are also commercially available.…”
Section: Quantum Dot Materialsmentioning
confidence: 99%
“…The reported quantum yields of the CdS x Se 1Àx nanoalloys vary from 3 to 85% depending on the synthesis methods. 10,[12][13][14][15] It was reported that the structural disorder induced by the excessive sulfur incorporated into the alloy reduced the quantum yield. 30 But, the disorder was not imaged even when the Z-STEM technique was exploited.…”
Section: The Optical Properties Of the Nanoalloysmentioning
confidence: 99%
“…A slow cooling rate results in large size disparities due to Ostwald ripening after the microwave power is removed. [29,30] Therefore, to reduce the influence of the cooling rate on the material properties, compressed air was used to cool the microwave cavity. Figure 3 shows UV/Vis absorption and the PL spectra of CdSe QDs obtained at different reaction times, but with the same growth temperature and power.…”
mentioning
confidence: 99%